TRACING OF SECONDARY METABOLITES AND ANTIMICROBIAL ACTIVITY OF SAPINDACEAE AS AN EFFORT TO PRESERVE HERBAL PLANTS: A REVIEW - Sanan, Antonius Oenunu; Hertiani, Triana; Murti, Yosi Bayu (Journal Pharmaceutical Science and Application; Vol 6 No 1 (2024): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2024.v06.i01.p01, 2024)
Background : Sapindaceae plants in the community are used to treat various diseases. This plant is traced to contain secondary metabolites with various pharmacological activities, including antimicrobials. Objective : This review article aims to provide information about Sapindaceae plants with antimicrobial potential and summarize the content of secondary metabolite compounds. Methods : This review article uses sources from international and national journals obtained by online search and considers two criteria, namely inclusion and exclusion. Then, it was further selected to obtain data in the form of secondary metabolites that can potentially be antimicrobial. Results : Some parts of the Sapindaceae plant contain essential secondary metabolites such as alkaloids, flavonoids, phenols, tannins, saponins, and triterpenoids. These secondary metabolites have a potential pharmacological activity that has been tested against antimicrobials. Conclusion : Sapindaceae plants contain diverse secondary metabolites and have antimicrobial activity. Further research is needed to explore other Sapindaceae plant species to find compounds and other pharmacological activities to address various diseases in the community.   Keywords : Sapindaceae; Secondary metabolite component; Antimicrobial Activity.